If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -6x = 4x + 0 Reorder the terms: 3 + -6x = 0 + 4x Remove the zero: 3 + -6x = 4x Solving 3 + -6x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 3 + -6x + -4x = 4x + -4x Combine like terms: -6x + -4x = -10x 3 + -10x = 4x + -4x Combine like terms: 4x + -4x = 0 3 + -10x = 0 Add '-3' to each side of the equation. 3 + -3 + -10x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -10x = 0 + -3 -10x = 0 + -3 Combine like terms: 0 + -3 = -3 -10x = -3 Divide each side by '-10'. x = 0.3 Simplifying x = 0.3
| 4(2x)=100 | | 42x-45=-72 | | 5x-1+9x=4x-7 | | (6+3x)=x-18 | | 6n+4=28-11 | | 4w^2+12w+9=1169 | | x^2-6x+9=64 | | y+6x=3 | | 7x+3y-8=4 | | 20w^2-31w+12=0 | | 16a^2-70a+49=0 | | 1x+2=-6 | | -4x^2=9x | | 5a+3(216+a)=888 | | 4y-7-6y-2= | | -2-2(-7x+7)=82 | | -15=-12+3r | | -7(1k-8)+2k= | | 2.5x+4=6x+4 | | 5x+5=6x+2 | | (c+3)(c+4)=2 | | 7x+3=-2x+21 | | Mp+mz=r | | lnx^7-10lnx=1 | | 3+2*[(2+1)*5+8]= | | -5x+2=-2x-31 | | 2y+6+8y+10+y+32=180 | | X^2+13x-64=0 | | 5m-28=-33+6m | | 3x^2+56=-136 | | 9n-23=17+n | | 2y^2-4y-8=y^2+y |